Kontroversi Seputar Tradisi Keagamaan Popular dalam Masyarakat Islam - Syafaq, Hammis (ISLAMICA: Jurnal Studi Keislaman, 2007)
This paper deals with a controversy concerning a popular religious practice that some âulama have been involved in. On this issue, the âulama are divided into those who reject it and those who accept it. Those who reject it are associated with the puritan Muslims who generally argue that the popular religious practices are form of bidâah. Among the puritans are Ibn TaymÃ®yah (d. 1328) and Muhammad âAbd al-Wahhab (d. 1791) the founding-father of WahhabÃ®yah school of thought in Najd, Saudi Arabia. Although the two have continuously waged an intellectual war on popular religious practices, these practices have nonetheless survived to this day.This paper proposes an approach that might be useful to the study of popular religious practices. It contends that the controversy on this issue may in fact be used as a framework in which the validity of certain religious tradition may be evaluated. A rejection toward certain religious practices is in fact deemed necessary as long as this is not destructive to the very structure of religion.On further note, the differences in opinion between those who reject and those who accept can actually be reconciled simply because the two have a lot in common in terms of their aims and final goals. They are not contradictive so far as the two are deemed as subjective efforts to understand the real meaning of Islam. On the ground that the two are a form of understanding, the one cannot be said as truer than the other just as the two cannot be said as representing the true teaching of the QurâÃ¢n and the Sunnah. Nonetheless, put together the two have indeed gave a more comprehensive picture of what Islam is all about.